2004
DOI: 10.1002/pssc.200405552
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport and magnetic properties of Co/Cu multilayers under the influence of In surfactant

Abstract: PACS 75.70.Cn The influence of In surfactant on the giant magnetoresistance (GMR) effect and magnetization processes has been investigated in Co/Cu thermally evaporated multilayers (MLs) with sublayer thicknesses of Co and Cu corresponding to the second antiferromagnetic maximum of interlayer coupling. Based on the Xray reflectivity (XRR) and atomic force microscopy (AFM) measurements it has been shown that In added in small amount at MLs interface leads to well ordered structures with small roughness (a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…These findings are supported by studies in rat brain, where it was observed to be involved in the incorporation of unsaturated fatty acids into phospholipids (Soupene et al 2010;Chen et al 2011). ACSL6 function was previously only described in neuronal cells (PC12) (Marszalek et al 2005) and in the brain from rats (Soupene et al 2010;Chen et al 2011). Consequently, we extend these initial findings using our rat model, where we further characterize the function of ACSL6 in skeletal muscle.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are supported by studies in rat brain, where it was observed to be involved in the incorporation of unsaturated fatty acids into phospholipids (Soupene et al 2010;Chen et al 2011). ACSL6 function was previously only described in neuronal cells (PC12) (Marszalek et al 2005) and in the brain from rats (Soupene et al 2010;Chen et al 2011). Consequently, we extend these initial findings using our rat model, where we further characterize the function of ACSL6 in skeletal muscle.…”
Section: Discussionmentioning
confidence: 98%
“…Application of a ML of Pb as a surfactant breaks down the coherent growth mode, disrupting the topographic correlation between the Co-Cu interfaces, and leads to creation of layers composed of small grains. Our atomic force microscope images taken for In surfactant [13] also demonstrated the small grain size in multilayers grown in the presence of a surfactant when compared to surfactant-free systems. This allows the conclusion that, in the present case also, the Bi and Pb surfactant segregation to the film surface results not only in smoother interfaces but also in diminishing the grain size.…”
Section: Discussionmentioning
confidence: 58%
“…Figure 2 shows the change of the surfactant concentration as a function of Co/Cu bilayer number. The squares correspond to experimental results and the circles represent theoretical calculations using formulae (4) and (5). A and C were fitted parameters in these simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of a small amount of surfactant into the Co/Cu multilayered system significantly reduces the degree of interfacial roughness [3]. The results showing the correlation between structural and magnetic properties of surfactant mediated Co/Cu multilayers were published elsewhere [4,5]. Smoothing of the interfaces is a result of surfactant segregation to the surface of the Co/Cu multilayers.…”
Section: Introductionmentioning
confidence: 87%